School Libraries in Modern Era: An Overview - Verma, Sharmila; Kumar, Adesh (Library Waves, 2015)
The school library is integral to the teaching and learning process. The school library facilitates the work of the classroom teacher and ensures each student has equitable access to resources, irrespective of home opportunities or constraints Schools are the base of education that directly develops a connection between secondary to senior secondary and after that senior secondary to higher education. Responsibility of the Librarian is to develop the keen interest for learning in students and assist as much as possible to teaching staff and others. Development of ICT has completely changed the Environment of the libraries, not only in operations even in sources of information also. This paper will show the various aspects about the paradigm shifting from print to digital and manual to automate. While the role of the school library remains constant, its design, digital platform, strategies and tools change as pedagogy and technology changes.